Establishment of a fluorescent reverse transcription-recombinase polymerase amplification assay for norovirus type GⅡ.4 - ZHENG Zhikun, XU Hefei, DING Wei, ZHANG Juan, DU Jiansen, HOU Lin, ZHANG Jin (精准医学杂志)
Objective To establish a fluorescent reverse transcription-recombinase polymerase amplification (RT-RPA) assay for norovirus (NoV) type GⅡ.4. Methods The NoV GⅡ.4 gene sequence was obtained from NCBI, and the primers and probes were designed by selecting the conserved regions after sequence alignment. With NoV GⅡ.4 standards as the detection object, the temperature, primer concentration, and probe concentration of the fluorescent RT-RPA reaction system were optimized to establish a fluorescent RT-RPA assay for NoV GⅡ.4. This method was assessed in terms of sensitivity, specificity, and clinical validation by detecting different concentrations of NoV GⅡ.4 standards and the nucleic acids of NoV GⅠ, other subtypes of NoV GⅡ (NoV GⅡ.2, NoV GⅡ.3, NoV GⅡ.7, NoV GⅡ.8, and NoV GⅡ.17), rotavirus, adenovirus, parechovirus, astrovirus, and sapovirus. Results The fluorescent RT-RPA assay had an optimal reaction temperature of 41 ℃, an optimal primer concentration of 630 nmol/L, and an optimal probe concentration of 240 nmol/L for detecting NoV GⅡ.4. And the limit of detection was 1×101 copies/μL for NoV GⅡ.4, the other nucleic acids did not produce the fluorescent signal that could be detected by the instrument. Conclusion This study establishes a fluorescent RT-RPA assay for NoV GⅡ.4, which is characterized by high sensitivity, good specificity, and rapid reaction speed, and it is expected to provide a new method for the rapid detection of NoV GⅡ.4 at ports.